The Portrayal of an Androgynous Female Protagonist in Louisa May Alcott’s Little Women - Ilahi, Shesa Kurnia; Suryani, Suci (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2025)
The presence of androgyny in literature, particularly in the context of feminism, offers an understanding of gender equality by demonstrating androgyny’s ability to break away from patriarchy and serve as a form of gender expression. Furthermore, this study aims to explore the oppression and struggles faced by Jo March in Louisa May Alcott’s Little Women (2018) as androgynous woman. The source of data in this study is from Louisa May Alcott’s Little Women (2018). The theory that is used in this study is radical-libertarian Feminism from Tong and Botts (2018) and characteristics of bitch from Freeman in Fahs’ book (2020). This study uses the theory of Miles & Huberman (2014) to conduct a qualitative analysis of the data, which includes data condensation, data display, and drawing and verifying conclusion. The data is collected from reading the novel Little Women by Louisa May Alcott (2018). The data of this study are derived from the monologue, dialogue between the characters, and the author’s narration. The first point of this study is finding out three types of oppression experienced by Jo March in Louisa May Alcott’s Little Women (2018) as androgynous woman such as mental oppression due to lack of freedom of choice, verbal oppression due to lack of freedom of voice, and social oppression due to lack of fashion. The second point of this study is knowing the result about Jo March’s struggle which reflects radical-libertarian feminism namely struggle for the idea and struggle for androgynous woman. The summary of the findings highlights how Jo can confront oppression in her patriarchy environment by becoming an androgynous woman who refuses to conform to traditional female norms in society, such as being a tomboy, refusing to marry, and not influencing the way traditional women behaves or dresses in general.